From pituitary adenoma to pituitary neuroendocrine tumor (PitNET): an International Pituitary Pathology Club proposal. Issue 4 (April 2017) - Asa, S L; Casar-Borota, O; Chanson, P; Delgrange, E; Earls, P; Ezzat, S; Grossman, A; Ikeda, H; Inoshita, N; Karavitaki, N; Korbonits, M; Laws, E R; et al.
Abstract : The classification of neoplasms of adenohypophysial cells is misleading because of the simplistic distinction between adenoma and carcinoma, based solely on metastatic spread and the poor reproducibility and predictive value of the definition of atypical adenomas based on the detection of mitoses or expression of Ki-67 or p53. In addition, the current classification of neoplasms of the anterior pituitary does not accurately reflect the clinical spectrum of behavior. Invasion and regrowth of proliferative lesions and persistence of hormone hypersecretion cause significant morbidity and mortality. We propose a new terminology, pituitary neuroendocrine tumor (PitNET), which is consistent with that used for other neuroendocrine neoplasms and which recognizes the highly variable impact of these tumors on patients.